Visualization of pesticide residue data - Yu Qin; Xiaoping Pang; Xi Zhao; Haiyan Liu; Fu Ren; Ce Bi; Dongjie Zhang; Jing Wu (Journal of Maps, 2017)
Compared to common data presentation methods such as tables and diagrams, thematic maps have the advantage of directly presenting complex, multidimensional spatial data. In this study, over 500 thematic maps are planned that present pesticide residue data from the inspection of fruit and vegetable samples. The data contain information on the samples, pesticides, sampling locations, maximum residue limits and inspection. Different calculation strategies are used to transform the original data into highly integrated data for cartography based on the demand investigation. During the map design process, standardized design should be used to ensure rigorous and consistent display of cartographic symbols. Two of the maps are used as examples to explain the data processing and map design procedures. The process can be used on all maps in this study and on more complex data.